2019
DOI: 10.1111/bph.14818
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene restores carbapenem susceptibility in New Delhi metallo‐β‐lactamase‐producing isolates by inhibiting the activity of New Delhi metallo‐β‐lactamases

Abstract: Background and PurposeBacteria producing New Delhi metallo‐β‐lactamase‐1 (NDM‐1) are an increasing clinical threat. NDM‐1 can inactivate almost all β‐lactams and is not sensitive to any existing β‐lactamase inhibitors. To identify effective inhibitors of the NDM‐1 enzyme and clarify the mechanism of action, a “lead compound” for developing more potent NDM‐1 inhibitors needs to be provided.Experimental ApproachNatural compounds were tested by enzyme inhibition screening to find potential inhibitors. MIC assays,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…The NDM-1-producing isolates E. coli ZC-YN3, K. pneumoniae QD-KP2 and E. coli BL21(DE3) (pET28a-NDM-1)( ndm-1 gene obtained from K. pneumoniae QD-KP2) were used as NDM-1-positive isolates for this study [19]. The NDM-1-negative strains E. coli BL21(DE3)(pET28a) and E. coli ATCC 25,922 were used as negative-control strains.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NDM-1-producing isolates E. coli ZC-YN3, K. pneumoniae QD-KP2 and E. coli BL21(DE3) (pET28a-NDM-1)( ndm-1 gene obtained from K. pneumoniae QD-KP2) were used as NDM-1-positive isolates for this study [19]. The NDM-1-negative strains E. coli BL21(DE3)(pET28a) and E. coli ATCC 25,922 were used as negative-control strains.…”
Section: Methodsmentioning
confidence: 99%
“…The NDM-1-negative strains E. coli BL21(DE3)(pET28a) and E. coli ATCC 25,922 were used as negative-control strains. In addition, E. coli ZC-YN5 (carried NDM-5) was described in our previous research [19].…”
Section: Methodsmentioning
confidence: 99%
“…Ebselen can simultaneously bind to two sites in NDM-1 by forming an S-Se bond with Cys221 and an amide bond with Lys224, thus selectively inhibiting MBLs both in vitro and in vivo . Another inhibitor of MBLs is pterostilbene 148 , a polyphenol compound that was isolated from red sandalwood. It has been used as a natural dietary antioxidant and in other applications such as anticancer.…”
Section: Recent Successes In the Fight Against Superbugsmentioning
confidence: 99%
“…Molecular dynamic simulation revealed that pterostilbene is localized to the catalytic pocket of NDM-1 by forming a strong interaction with Trp93 and Asp124. Consequently, this hinders substrate binding to NDM-1 and reduces NDM-1 activity 148 . Furthermore, a high-throughput assay revealed that the inhibitor of topoisomerase II mitoxantrone effectively suppressed enzymatic activity of VIM 149 , through unknown mechanisms.…”
Section: Recent Successes In the Fight Against Superbugsmentioning
confidence: 99%
“…Infections caused by carbapenem-resistant Enterobacteriaceae (CRE), especially the New Delhi metallo-β-lactamases (NDM)-producing Escherichia coli, have become a global therapeutic challenge in clinical and public health settings (Perez and Bonomo, 2018). In general, isolates carrying bla NDM tend to carry other resistance genes thus limiting treatment options (Falagas et al, 2014;Liu et al, 2019). Currently, the polymyxin antibiotics (polymyxin B and colistin) have reemerged as the last-line therapy against CRE.…”
Section: Introductionmentioning
confidence: 99%